Learning to Argue and Arguing to Learn: Argument‐Driven Inquiry as a Way to Help Undergraduate Chemistry Students Learn How to Construct Arguments and Engage in Argumentation During a Laboratory Course. Issue 5 (25th March 2013) - Walker, Joi Phelps; Sampson, Victor
Abstract This study examines whether students enrolled in a general chemistry I laboratory course developed the ability to participate in scientific argumentation over the course of a semester. The laboratory activities that the students participated in during the course were designed using the Argument‐Driven Inquiry (ADI) an instructional model. This model gives a more central place to argumentation and the role of argument in the social construction of scientific knowledge. The development of the students' ability to construct a scientific argument and to participate in scientific argumentation was tracked over time using three different data sources. These data sources included a performance task, which was administered at the beginning, middle, and end of the course, video recording of the students participating in episodes of argumentation, and the lab reports the students wrote as part of each lab activity. As time was the independent variable in this study, a repeated measure ANOVA was used to evaluate changes in the ways students performed on each task over the course of the semester. The results of the analysis indicate that there was significant growth in the quality of the students' written arguments and nature of their oral argumentation. There also was a significant correlation between written and oral arguments. These results suggest that the use of an integrated instructional model that places emphasis on argument and argumentation can have a positive impact on the quality of the arguments students include in their investigation reports, the argumentation they engage in during lab activities, and their overall performance on tasks that require them to develop and support a valid conclusion with genuine evidence. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50: 561–596, 2013